Pengaruh Perceived Usefullness, Perceived Ease of Use Terhadap Behavioral Intention To Use dengan Atittude Towards Using sebagai Variabel Intervening (Studi Kasus Pada Gopay Dikota Yogyakarta) - Rena Eka Setyawati (Program Studi Manajemen Fakultas Ekonomi UST, 2020)
This study aims to determine (1) the effect of perceived usefulness on attitude towards using and, (2) the effect of perceived ease of use on attitude towards using (3) the effect of attitude towards using on behavioral intention to use (4) the effect of perceived usefulness on behavioral intention to use (5) the effect of perceived ease of use on behavioral intention to use (6) the effect of perceived usefulness and perceived ease of use on attitude towards using (7) the effect of perceived usefulness and perceived ease of use on behavioral intention to use. The sample in this study were 115 students of the Faculty of Economics, University of Sarjanawiyata Tamansiswa Yogyakarta, users of GOPAY. The data collection method uses a questionnaire method that is distributed using the Accidental Purposive Sampling technique. In this research, data quality test, classical assumption test (normality test, multicollinearity test and heterokesdasticity test) are used, multiple linear regression analysis and hypothesis testing. The results of the study show that the perceived usefullness variable influences the attitude towards using, the perceived ease of use variable influences the attitude towards using, the attitude towards using variable influences the behavioral intention to use, the perceived usefullness variable influences the behavioral intention to use, the perceived ease of use variable influence on behavioral intention to use, the variable perceived usefulness and perceived ease of use influence the attitude towards using, the variable perceived usefulness and perceived ease of use affect the behavioral intention to use. Keywords: GOPAY, perceived usefulness, perceived ease of use, attitude towards using, behavioral intention to use.